2000
DOI: 10.1016/s0893-133x(00)00150-0
|View full text |Cite
|
Sign up to set email alerts
|

WAY 100135, an Antagonist of 5-HT1A Serotonin Receptors, Attenuates Psychotomimetic Effects of MK-801

Abstract: Non-competitive antagonists of NMDA receptors such as phencyclidine (PCP) or ketamine are known for their strong, frequently neuroleptic-resistant psychotomimetic effects in humans (Javitt and Zukin 1991). These clinical effects, as well as evidence suggesting the involvement of NMDA receptors in the pathophysiology of schizophrenia (Carlsson et al. 1999;Harrison 1999;Wachtel and Turski 1990), support the experimental modeling of psychoses by administration of non-competitive NMDA receptor antagonists (Jentsch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 75 publications
2
37
1
Order By: Relevance
“…Motor activity. Motor activity was recorded in an Opto-Varimex apparatus linked to an IBM PC (Columbus Instruments, Columbus, OH) according to the method described by Wedzony et al (20). The apparatus consisted of a cage (42 ϫ 42 ϫ 30 cm) equipped with 15 infrared emitters (spaced at 2.65-cm intervals) located on the x and y axes 2-3 cm above the floor of the cage (depending on the size of the animal) and an equivalent number of receivers located on the opposite walls.…”
Section: Methodsmentioning
confidence: 99%
“…Motor activity. Motor activity was recorded in an Opto-Varimex apparatus linked to an IBM PC (Columbus Instruments, Columbus, OH) according to the method described by Wedzony et al (20). The apparatus consisted of a cage (42 ϫ 42 ϫ 30 cm) equipped with 15 infrared emitters (spaced at 2.65-cm intervals) located on the x and y axes 2-3 cm above the floor of the cage (depending on the size of the animal) and an equivalent number of receivers located on the opposite walls.…”
Section: Methodsmentioning
confidence: 99%
“…We recorded motor activity in an Opto-Varimex cage (Columbus Instruments, Columbus, Ohio) linked to a computer and placed in a sound-attenuated room illuminated by a 20-W white light. The amount of time spent in ambulatory activity was analyzed using an Auto-Track software 42,43 (Columbus Instruments, Columbus, Ohio). Session duration was 20 min for adult rats and 60 s for 10-day-old pups.…”
Section: Synthesis Of Inhibitorsmentioning
confidence: 99%
“…Functionally, 5-HT 1A receptor agonism produces effects similar to those produced by 5-HT 2A receptor antagonism (for review, see Meltzer and Huang 2008). The importance of 5-HT 1A receptors to the action of NMDAR antagonist-induced locomotor activity and cognitive impairment has been suggested by Hönack (1992, 1993) and by Wedzony et al (2000).…”
Section: -Ht 1a Receptors and Blockade Of Nmdar Antagonist Effects Omentioning
confidence: 99%
“…This is due, in part, to studies of the role of 5-HT in attenuating or exacerbating a wide range of behavioral and biochemical effects of N-methyl-D-aspartate (NMDA) receptor (NMDAR) non-competitive antagonists, e.g., phencyclidine (PCP), dizocilpine , and ketamine, in rodent and non-human primate models for schizophrenia, and for understanding the mechanism of action of APDs. Early studies suggested that 5-HT release, and 5-HT 1A and 5-HT 2A receptors were important, along with glutamate and DA, to understanding and the actions of NMDAR antagonists and developing effective treatments based upon that knowledge (Schmidt and Fadayel 1996;Varty et al 1999;Wedzony et al 2000). Clarifying the importance of 5-HT to the actions of NMDAR antagonists is important because of the evidence that the non-competitive NMDAR antagonists more faithfully reproduce the full spectrum of the psychopathology (both positive and negative symptoms) and the cognitive impairment associated with schizophrenia (Lahti et al 1995;Malhotra et al 1997b;Gouzoulis-Mayfrank et al 2005;Coyle 2006;Javitt 2007) than either dopaminergic agents such as amphetamine (Davis et al 1991), or serotonergic agents, such as LSD or N,N-dimethyltryptamine (Geyer and Vollenweider 2008).…”
Section: Introductionmentioning
confidence: 99%